Prevalence of metallo-beta-lactamases (MBLS) producing Pseudomonas aeruginosa in hospitalized patients in rural tertiary care hospital in Uttar Pradesh, India - Sinha, Sarita; Singh, Amit; Verma, Rajesh Kumar; Singh, Dharmendra Prasad; Kumari, Sunita (International Journal of Research in Medical Sciences, 2018)
Background: Pseudomonas aeruginosa is a leading cause of nosocomial infections due to MBLs production with limited therapeutic options, higher rate of colonization is encountered in hospitalized patient streated with broad spectrum antibiotics. This study was conducted with an aim to know the prevalence of Carbapenem resistant MBLs producing strains of Pseudomonas aeruginosa in hospitalized patients. Methods: A total of 14700 samples were obtained from various wards during Jan 2016 to June 2017, were screened for P. aeruginosa by conventional culture and biochemical tests. All confirmed P. aeruginosa isolates were further subjected to Modified Kirby- Bauer disc diffusion test as per CLSI guidelines. All IPM resistant isolates were screened for MBL production by DDST, CDST, MHT and E-test MBL. Results: Atotal of 1423were identified as P. aeruginosa. The isolation rate of P. aeruginosa at our hospital was 9.7%. Among these, 130(9.1%) isolates were IPM resistant. A total of 111 (85.4%) were MBL positive by CDST and E-test, 92 (70.5%) by DDST and 80 (61.5%) by MHT. The prevalence of MBL producing P. aeruginosa was 111/1423(7.8%) while among IPM resistant P. aeruginosa, its prevalence was 111/130 (85.4%). Conclusions: The study documents presence of nosocomial MBL producing P. aeruginosa strains in our Institute. E-test and CDST were superior to DDST and MHT for detection of MBLs.